(untitled) (Western Pacific Surveillance and Response, 2021)
The rainy season in the Philippines is from June to October; this is when the number of dengue cases typically increases. In 2020 during this time, the world was facing the threat of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Coronavirus disease 2019 (COVID-19) and dengue viral infections have similar presentations and laboratory findings, including fever and thrombocytopenia, and there have been reports of coinfection with SARS-CoV-2 and arthropod-borne virus. Here, we report a case of SARS-CoV-2–dengue virus coinfection in the Philippines in a female aged 62 years, whose early symptom was fever and who was positive for SARS-CoV-2 and positive for dengue. Early recognition of such coinfection is important so that proper measures can be taken in the management of the patient.